Encyclopedia of Medical Devices and Instrumentation 2006
DOI: 10.1002/0471732877.emd015
|View full text |Cite
|
Sign up to set email alerts
|

Bioheat Transfer

Abstract: This article presents the characteristics of bioheat transfer that distinguish it from nonliving systems, including the effects of blood perfusion on temperature distribution, coupling with biochemical processes, therapeutic and injury processes, and thermoregulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…The thermal effect due to the absorbed incident light is modeled using the bioheat transfer mechanism [40]. The algorithm analyzes the temperature distribution and heating profile when the heat is applied to the tissue.…”
Section: Methodsmentioning
confidence: 99%
“…The thermal effect due to the absorbed incident light is modeled using the bioheat transfer mechanism [40]. The algorithm analyzes the temperature distribution and heating profile when the heat is applied to the tissue.…”
Section: Methodsmentioning
confidence: 99%
“…All heat transfer between tissue and blood is assumed to occur in the capillary bed. Many studies have shown this to be erroneous and more complex and rigorous models of heat transfer within tissue have been developed [50][51][52]. An excellent review of bioheat transfer models is provided in [53].…”
Section: Heat Transfer In Tissuementioning
confidence: 99%
“…37 Three major mechanisms of heat exchange participate in the thermal energy balanceconvection, conduction, and radiation, in addition to a phase change, evaporation. The conservation of energy within the human body poises the internal production (sources) and loss (sinks; e.g., [105]):…”
Section: Bioheat Transfer In Physiology and Pathologymentioning
confidence: 99%